Latin American Labor Markets in the 1990s: Deciphering the Decade - Suzanne Duryea; Olga Lucia Jaramillo; Carmen Pagés-Serra (Inter-American Development Bank, Research Department, 2003)
This paper analyzes the recent performance of Latin American labor markets. We find that unemployment rates are on the rise in most countries and sub-regions of Latin America. The rise in unemployment over the 1990s is not driven by a higher proportion of women, adults or urban workers in the labor force, nor can it be attributed to an increasing demand for skilled workers. In a few countries, increasing unemployment is caused by falling employment rates. In the rest, unemployment rates can be explained by a large rise in participation that has not been fully absorbed by increases in employment. We also find that a large and in many countries growing proportion of workers are employed at jobs that pay very low wages. Finally, returns to higher education are increasing while returns to secondary education are declining in almost all countries.
Keywords: 330; Arbeitsmarkt; Arbeitslosigkeit; Lateinamerika